2020
DOI: 10.1093/ehjci/jez319.610
|View full text |Cite
|
Sign up to set email alerts
|

P980 RV longitudinal dysfunction predicts outcomes in anterior ST elevation myocardial infarction treated by primary PCI

Abstract: Funding Acknowledgements This work was supported by CREDO Project - ID: 49182, financed through the SOP IEC -A2-0.2.2.1-2013-1 cofinanced by the ERDF Background The prognostic value of LV function in the setting of an acute ST elevation myocardial infarction (STEMI) is well established, but data regarding the association between RV function and adverse events in this population of patients are still scarce, especially for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The 2D RV strain is shown to be significantly and independently related to ventricular arrythmias and sudden cardiac death in patients with acute MI [104]. A study by Zamfir, D. et al showed that RVFWLS (OR: 1.04; 95% CI: 0.21-5.08) and 3D-RVEF (OR: 0.83; 95% CI: 0.20-3.43) were predictive for in hospital major adverse cardiovascular events regardless of the culprit coronary artery [105].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…The 2D RV strain is shown to be significantly and independently related to ventricular arrythmias and sudden cardiac death in patients with acute MI [104]. A study by Zamfir, D. et al showed that RVFWLS (OR: 1.04; 95% CI: 0.21-5.08) and 3D-RVEF (OR: 0.83; 95% CI: 0.20-3.43) were predictive for in hospital major adverse cardiovascular events regardless of the culprit coronary artery [105].…”
Section: Myocardial Infarctionmentioning
confidence: 99%